1988
DOI: 10.1051/rnd:19880801
|View full text |Cite
|
Sign up to set email alerts
|

On the role of epididymal factors in sperm fertility

Abstract: Notwithstanding our improved descriptive knowledge of events occurring to mammalian sperm during epididymal maturation, the nature of the mechanisms involved in the development of such primary functions as forward motility (Bedford, 1975) and zona pellucida recognition (Saling, 1982) remain obscure.This review attempts to summarize the latest information produced by our laboratory in relation to the interaction of epididymal products with spermatozoa and the bearing that this interaction might have on sperm fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…It is believed that the functionality of spermatozoa is largely dependent on the post-translational modifications of proteins in the absence of de novo protein synthesis. This occurs during epididymal maturation and post-ejaculatory capacitation of spermatozoa in the female reproductive tract (Blaquier et al 1988a(Blaquier et al , 1988b. The main function of a spermatozoon is to travel through the female genital tract, traverse the zona pellucida of an oocyte and finally deliver the male haploid genome to the oocyte during fertilisation.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that the functionality of spermatozoa is largely dependent on the post-translational modifications of proteins in the absence of de novo protein synthesis. This occurs during epididymal maturation and post-ejaculatory capacitation of spermatozoa in the female reproductive tract (Blaquier et al 1988a(Blaquier et al , 1988b. The main function of a spermatozoon is to travel through the female genital tract, traverse the zona pellucida of an oocyte and finally deliver the male haploid genome to the oocyte during fertilisation.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, the acquisition of functional competence during capacitation occurs in the complete (Engel et al, 1973;Hernandez-Perez et al, 1983) or virtual (Gur and Breitbart, 2006) absence of gene transcription and translation. Thus, whereas incubation of human, mouse, rat and bovine spermatozoa with radiolabeled amino acids has recently revealed evidence of limited protein synthesis in these cells, the general consensus is that the acquisition of functionality during capacitation is largely dependent on posttranslational modifications to pre-existing proteins (Blaquier et al, 1988a;Blaquier et al, 1988b;Ross et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, the epididymis is known to play an important part in the maturation of sperm cells and their ability to fertilize eggs (Bedford, 1967;Orgebin-Crist, 1967;Glover & Nicander, 1971; and reviews by Cooper, 1986Cooper, , 1990Robaire & Hermo, 1988;Blaquier et al, 1988Blaquier et al, , 1989. However, some authors have suggested that the human sperm cells do not have to be present in and traverse the epididymis in order to attain motility and develop into mature cells (Adler & Makris, 1951;Silber 1980Silber , 1989a.…”
Section: Introductionmentioning
confidence: 99%